A case report: metastatic complete heart block. Issue 4 (29th November 2018) - Kumar, Dhiraj; Mankame, Pooja; Sabnis, Girish; Nabar, Ashish
Abstract: Background: Though primary malignant tumours of the heart are rare, secondary metastatic affection of the heart is quite common. Common presentations include pericardial effusion, obstruction of inflow and outflow tracts and arrhythmias, most notably tachyarrhythmias, and very rarely complete heart blocks (CHBs). Case summary: A 28-year-old man suffering from carcinoma of the tongue underwent a surgery in the form of radical hemimandibulectomy. He presented with recurrent syncope and CHB with broad complex escape rhythm. After performing echocardiography, he was found to have malignant infiltration of the interventricular septum. This was confirmed by performing cardiac positron emission tomography (PET). It was decided that a permanent pacemaker would then be implanted. Post-implantation of permanent pacemaker patient succumbed to massive haemoptysis after 5 days. Discussion: Although CHBs are rare in malignancy and careful assessment of ECGs especially looking for first degree heart blocks which may progress to CHB later on is prudent. One must rule out hypercalcaemia as it is a reversible cause of CHB. Careful echocardiogram can show hyper enhancement on interventricular septum and presence of pericardial effusion. Further imaging like cardiac magnetic resonance imaging or cardiac PET is confirmatory.